SMARTAUTOMATICCOINDISPENSINGMECHANISM - Salaheddinen Boughani; Aouatef Douaibia (My University, 2025)
With the rapid technological advancement, automated systems have become effective tools to improve daily operations and reduce errors. This project aims to develop a smart device that automaticallyreturns cash change without human intervention, byanalyzing the entered amount and selecting the appropriate denominations using dedicated containers for each, whilereading the cash level in each container. The mechanical parts were designed using FreeCAD and printed with a 3D printer, while Wokwi was used for simulating and programming the electronic circuits. This device can be used in buses, shops, and potentially integrated with ATMs to enhance user experience and the accuracy of financial operations. ----------------------------------------------------------------------------- فًي ظلال تطور التكنولوجًي ،أصبحت الأنظمة الآليةٌ أداة فعّالة لتحسينٌ العمليات اليوٌميةٌ و تقليلٌ الأخطاء. يهٌدف هذا المشروع إلى تطويرٌ جهاز ذكًي يقٌوم بإرجاع الصرف النقدي بشكل تلقائيً دون تدخل بشري ،من خلال تحليلٌ المبلغ المُدخل و اختياٌر الفئات النقديةٌ المناسبة باستخدام حاوياٌت مخصصة لكل فئة وقراءة مستوى نقودكل وعاء. تم تصممٌ الأجزاء المكٌانيكٌةٌ باستخدام برنامج Free CAD وطُبعت بواسطةطابعة ثلاثةٌ الأبعاد ،بينٌما استُخدم Wokwi لمحاكاة الدوائر الإلكترونةٌ وبرمجتها. يمُكن استخدام هذا الجهاز فًي الحافلات ،المحلات،وإمكانيةٌ دمجه مع أجهزة الصراف لتحسينٌ تجربة المستخدم ودقة العملياٌت الماليةٌ. ----------------------------------------------------------------------------- Avecl’avancementrapidedelatechnologie,lessystèmesautomatiséssontdevenusdesoutilsefficaces pour améliorer les opérations quotidiennes et réduire les erreurs. Ceprojetviseàdévelopperundispositifintelligentcapablederendreautomatiquementlamonnaiesans intervention humaine, en analysant le montant saisi et en sélectionnant les coupures appropriées à l’aide de compartiments dédiés à chaque dénomination, tout en surveillant le niveau de liquidités dans chaque compartiment. LespiècesmécaniquesontétéconçuesavecFreeCADetimpriméesàl’aided’uneimprimante3D, tandis que Wokwi a été utilisé pour la simulation et la programmation des circuits électroniques. Cedispositifpeutêtreutilisédanslesbus,lesmagasins,etpotentiellementintégréauxdistributeurs automatiques afin d’améliorer l’expérience utilisateur et la précision des opérations financières
Keywords: Automatic; SmartDevice; CashReturn; Mechanics; Electronics; FreeCAD; 3DPrinter; Wokwi; Automation; Electronic Simulation.; أوتوماتيكٌ ،صرف آليً،جهاز ذكًي ،مكٌانيكٌ، إلكترونيكٌ ،FreeCAD، طابعة ثلاثيةٌ الأبعاد ،Wokwi،أتمتة، محاكاة إلكترونيةٌ; Automatique; Dispositif intelligent; Rendude monnaie; Mécanique; Électronique; Imprimante 3D; Automatisation; Simulation électronique